Traveler’s Cafe: Exploring How One’s Level of Emotional Maturity Has an Impact in Their Decision to Marry - Candy Truisnaningsih (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
Chick Lit usually focus on how the main character finally finds her true love after several times meeting the wrong guy. However, through the issues of marriage that I make, I am stressing more on their psychological emotional maturity before they decide to get married. The story talks about a woman who has a boyfriend but not ready to marry him. She captured in her own insecurities about being a wife. Her situation gets worse when she rejected the proposal and her family found out. The story will revolve around the emotional journey of the problem and slowly reveals the changing behavior and her ways of thinking. Hopefully this work will remind people to look the idea of how important it is to see that marriage is not about age. To understand how psychological emotional maturity works, six levels of maturity are used as the main theory in this work.